2019
DOI: 10.1002/slct.201900921
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Water Extraction of Phenolic Compounds and Analysis of Inorganic Elements from Erigeron breviscapus

Abstract: Subcritical water extraction of 13 phenolic compounds from Erigeron breviscapus has been studied using statically single factor experimental design. Results indicate high yields of the phenolic compounds except scutellarein and apigenine obtained at temperatures ranging from 100 to 140 °C. Box–Behnken experimental design (BBD) on three levels and three significant variables was used for optimization of total flavonoids and the antioxidant activities measured by a free radical method (DPPH). The amounts of tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…BBD was used to analyze the experimental data, and the second-order polynomial model was obtained using Design–Expert. The model was obtained by BBD after variance analysis. …”
Section: Methodsmentioning
confidence: 99%
“…BBD was used to analyze the experimental data, and the second-order polynomial model was obtained using Design–Expert. The model was obtained by BBD after variance analysis. …”
Section: Methodsmentioning
confidence: 99%
“…Glycosides extracted by SBWE have been proven to have antioxidant activities and tyrosinase inhibitory activity, as shown in Table 4 [ 36 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]. Gao et al [ 144 ] has performed SBWE of phenolic compounds from pomegranate seed residues at 80–280 °C.…”
Section: Compounds Extracted By Subcritical Watermentioning
confidence: 99%
“…TP and antioxidant capacities of SBWE (120 °C) were not as high as organic solvents; however, with respect to the extraction time (2 h for leaching vs. 30 min for SBWE) and toxicity, subcritical water is more acceptable. Meng and Cheng [ 149 ] have studied 13 phenolic compounds and 20 inorganic elements of Erigeron breviscapus . They also have found similar results, as the glycosides are not stable at a high temperature and with a long extraction time.…”
Section: Compounds Extracted By Subcritical Watermentioning
confidence: 99%
“…demonstrated the application of subcritical water for the recovery of macro‐nutrients and micro‐nutrient elements from dried leaf powder of Moringa oleifera [32] and Meng and Cheng used it for the simultaneous extraction of phenolic compounds and inorganic elements from Erigeron breviscaous . [33] Supercritical fluids have also been used for coal desulfurization and early work reported the removal of both inorganic and organic sulfur compounds from coal at temperatures above 350 °C. [ 21 , 22 , 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] Nuapia et al demonstrated the application of subcritical water for the recovery of macronutrients and micro-nutrient elements from dried leaf powder of Moringa oleifera [32] and Meng and Cheng used it for the simultaneous extraction of phenolic compounds and inorganic elements from Erigeron breviscaous. [33] Supercritical fluids have also been used for coal desulfurization and early work reported the removal of both inorganic and organic sulfur compounds from coal at temperatures above 350 °C. [21][22][23] A systematic method for desulfurization through extraction with a mixture of ethanol and water in varying proportions at temperatures above 350 °C has been reported by Azzam and Lee, [21] but the optimized conditions resulted in the solvent being reactive that in turn degraded the coal as seen from CÀ C bond cleavage in the coal structure.…”
Section: Introductionmentioning
confidence: 99%